ANALISIS STRUKTUR DAN KEBAHASAAN TEKS FABEL SERTA PEMANFAATANNYA SEBAGAI BAHAN AJAR TEKS FABEL DI SMP - Ismi Izzati (CV. ADIBA AISHA AMIRA, 2023)
The purpose of this study is to make teaching materials for fable texts for class VII SMP. Teaching materials prepared in advance through the text analysis stage. The analysis was carried out so that the material presented in teaching materials was at the level of understanding of students. After text analysis, the teaching materials were validated by expert lecturers from the Indonesian Language Education Study Program, Indonesian teachers and junior high school students as respondents. This study refers to the descriptive analytic method which aims to describe the results of the validation and testing of fable text book subchapters for class VII students of junior high school. The data obtained came from the results of expert lecturer validation questionnaires, validation of Indonesian language teachers, and student responses. The data obtained from the results of the questionnaire obtained successive percentages, 95.97%, 96.65% and 92.75%. Then the results of the questionnaire are added up and get the final result of 95.05%. The percentage of final results shows that the eligibility criteria for fable text book subchapters are very valid and appropriate to be used as material for learning fable texts.